PERLINDUNGAN HUKUM KONSUMEN DEPO AIR MINUM ISI ULANG YANG HAKNYA DILANGGAR DI KOTA SEMARANG - Galuh Puspa Prameswari; Fitika Andraini (Fakultas Hukum Universitas Stikubank, 2020)
In our daily needs as a human being cannot be separated from the natural resource that is bestowed by God Almighty, especially water. People choose to consume drinking water produced by the Drinking Water Depot (AMD) business because of the need for clean and healthy water for consumption. But it turns out that health is not always guaranteed because the drinking water produced by the drinking water depot (AMD) refills is still found many germs that cause disease (pathogens) and is not safe for consumption because it does not meet the standard of eligibility. Issues to be discussed are the legal protection of consumers for their rights being violated by business actors in refill drinking water depots in Semarang City, and the settlement mechanisms that can be taken to resolve various violations of refilled drinking water depots that do not have a business license in Semarang City. The approach method used in this research is a normative juridical approach using secondary data in the form of library materials, documents, and other laws and regulations related to the research that will be discussed. And the analysis technique used is descriptive analytical. Legal Protection for Water Depot Consumers whose Rights are Violated by Business Actors of Refill Drinking Water Depot in Semarang City, are regulated in Article 60 and Article 62 of the Consumer Protection Law as well as in Article 28 of the Regulation of the Minister of Health of the Republic of Indonesia Number 736 / Menkes / Per / IV / 2010 concerning Procedures for Supervision of Drinking Water Quality, while the Settlement Mechanism that Can Be Taken to Resolve Various Violations of Refill Drinking Water Depots that Do not Have Business Permits in Semarang City are regulated in Article 47 and Article 48 of the Consumer Protection Law. Keywords: Consumer Protection, Drinking Water Depot (AMD), Business License